Role of recreated habitats in butterfly conservation: a case study at Thenmala, Kerala, India - V.S. Revathy; George Mathew and T.P. Narayanankutty (International Journal of Tropical Insect Science, 2014)
Focal species are valuable tools for evaluating management practices for biodiversity conservation. Butterfly gardening through the creation of appropriate habitats can be a primary conservation tool to increase species abundance and richness and gene flow among the populations in fragmented landscapes. In this context, the role of butterfly gardens in the conservation of butterfly populations and the seasonal population trends of swallowtail butterflies (family Papilionidae) sighted in the Butterfly Safari Park at Thenmala were studied. A total of 4760 sightings of 15 species of swallowtails belonging to five genera were recorded, of which six were endemic species, three species had protected status and two were rare species. It is worth noting that of the 19 species of the papilionids recorded in Kerala, as many as 15 species were recorded in Thenmala. Of the various species recorded, Troides minos, Pachliopta pandiyana, Pachliopta aristolochiae, Graphium agamemnon, Graphium sarpedon, Papilio polytes, Papilio clytia, Papilio demoleus and Papilio polymnestor comprised the resident populations, while species such as Atrophaneura hector, Papilio helenus, Papilio dravidarum, Papilio paris, Papilio liomedon and Graphium nomius were found only during certain seasons. The overall butterfly abundance was high from August to November. The butterfly populations exhibited a gradual decline in numbers from December onwards with the onset of dry seasons. The abundance of butterfly populations was low during March– April. The abundance of T. minos, P. pandiyana, P. polymnestor, P. paris, P. dravidarum, P. helenus, P. polytes and P. liomedon showed a significant negative correlation with monthly average temperature and a significant positive correlation with humidity.